The taxonomy of the Japanese oak red scale insect, Kuwania quercus (Kuwana) (Hemiptera: Coccoidea: Kuwaniidae), with a generic diagnosis, a key to species and description of a new species from California - Wu, San’an; Nan, Nan; Gullan, Penny; Deng, Jun (Zootaxa, 2013)
The oak red scale insect, Kuwania quercus (Kuwana), was described from specimens collected from the bark of oak trees (Quercus species) in Japan. More recently, the species has been identified from California and China, but Californian specimens differ morphologically from Japanese material and are considered here to be a new species based on both morphological and molecular data. In this paper, an illustrated redescription of K. quercus is provided based on type specimens consisting of adult females, first-instar nymphs and intermediate-stage females, and a lectotype is designated for Sasakia quercus Kuwana. The new Californian species, Kuwania raygilli Wu & Gullan, is described and illustrated based on the adult female, first-instar nymph and intermediate-stage female. A new generic diagnosis for Kuwania Cockerell based on adult females and first-instar nymphs, and a key to species based on adult females are included.